PENGARUH TOTAL ASET DAN TINGKAT HUTANG TERHADAP TARIF PAJAK EFEKTIF DI PERUSAHAAN BUMN YANG TERCATAT PADA BURSA EFEK INDONESIA - Fatmawati, Ade Pipit; Aprillia, Eunike (LAND JOURNAL, 2024)
In Indonesia, the largest capacity to support the needs of the state is taxes. The company is part of the corporate tax subject. The aim to find effect of total assets and debt leveels to effective taxrates inBUMN liisted in Indonesia Stock Exchange. Researchers use quantitattive methods and associative problem formulation in the form of cause and effect. Using purposive sampling part of the type of non-probability sampling obtained 50 data. DescriptiveStatistics, ProductMoment Correlation Analysiis, MultipleCorrelation Analysiis, Multiiple Regression Analysiis, CoefficientDetermination Analysiis, PartialHypothesis Testiing, and SimultaneousHypothesis Testing areuse anaalyze data. The results show that total assets have effect to effectivetax rate, debt rate has no effect to effective taxrate and total assets and debt rate have an effect on the effeective taxrate simultaneously.